2000
DOI: 10.1088/0963-0252/9/3/310
|View full text |Cite
|
Sign up to set email alerts
|

Negative ions and the role of metastable molecules in a capacitively coupled radiofrequency excited discharge in oxygen

Abstract: Axial distributions of negative oxygen ions in an asymmetric, capacitively coupled oxygen radiofrequency discharge (of the gaseous electronics conference reference cell type) are investigated. The O − ion densities are measured by detecting the electrons released after photo-detachment with a Langmuir probe.At small power and a pressure of approximately 10 Pa the axial distributions of both the O − ions and the electrons are flat. At higher power (characterized by voltage amplitudes in excess of 200 V) both qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
88
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(101 citation statements)
references
References 43 publications
12
88
1
Order By: Relevance
“…6͑b͒, the plasma potential increases with increasing voltage and the sheath length also increases because of the confinement of O − by the increased plasma potential. The radial distribution of electron and O − , and the O − /O 2 + density ratio calculated by the 1D PIC-MCC simulation are consistent with the experimental data of Katsch et al 14 Figure 7 shows the charged species density, potential, and electron temperature with the ratio of Ar to O 2 at 115 mTorr and 160 V. As the ratio increases, the concentration of electrons and Ar + increases due to the increase of background argon atoms T n is the neutral gas temperature in K.…”
Section: B Comparison Between 1d Pic-mcc Simulations and Experimentssupporting
confidence: 88%
See 1 more Smart Citation
“…6͑b͒, the plasma potential increases with increasing voltage and the sheath length also increases because of the confinement of O − by the increased plasma potential. The radial distribution of electron and O − , and the O − /O 2 + density ratio calculated by the 1D PIC-MCC simulation are consistent with the experimental data of Katsch et al 14 Figure 7 shows the charged species density, potential, and electron temperature with the ratio of Ar to O 2 at 115 mTorr and 160 V. As the ratio increases, the concentration of electrons and Ar + increases due to the increase of background argon atoms T n is the neutral gas temperature in K.…”
Section: B Comparison Between 1d Pic-mcc Simulations and Experimentssupporting
confidence: 88%
“…Figure 1͑b͒ corresponds to a 1D PIC-MCC simulation in an asymmetric cylindrical voltage-driven capacitively coupled discharge. Simulations for this reactor are compared with the experimental data obtained by Katsch et al 14 Here, the effects of gas composition and driving voltage are shown. Figure 1͑c͒ corresponds to the twodimensional model used for the fluid simulations of the reactor used by Kiehlbauch et al in Ref.…”
Section: Simulation Conditionsmentioning
confidence: 99%
“…[27,30]. Ignoring the electric asymmetry between the powered and grounded electrode, this part of the discharge can be simulated by the planar, one-dimensional model shown in figure 1.…”
Section: Methods Of Simulationmentioning
confidence: 99%
“…It can be, for instance, accompanied by a double layer (internal sheath [20]). Electro-negative gas discharges are thus rather complex and the investigation of the spatio-temporal structure of the discharge as a function of external control parameters (current, voltage, frequency, pressure, and geometry) is a great theoretical [21,22,23,24] and experimental [25,26,27,28,29,30] challenge. In addition, electro-negative processing gases are reactive molecular gases, with internal degrees of freedom, which lead to a quite involved plasma chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation